Design of protection schemes based on symmetrical components in the time domain (2021)
Symmetrical components theory, presented by Fortescue in 1918, and its analysis of the time domain presented by Lyon in 1954, have been widely used for fault analysis and power system protection algorithms. In recent times, applications in time domain have been deeply studied given their potential for getting a quicker failure detection, there are two main techniques which apply signal processing methods in the time domain: Travel-wave and incremental quantities. The theoretical background of symmetrical components to fault analysis is well recognized. This paper presents a new algorithm that allows detecting direction and gives an indication for a fault location, based on the calculation of the symmetrical components and processing them as incremental quantities, the algorithm is tested in a simulation study case and on the data provided by a relay for a real-world fault.